2009
DOI: 10.1177/0192513x09339478
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Nature of Family Resilience in Families Affected by Parental Alcohol Abuse

Abstract: Resilient families are able to adapt to adversities, but the nature of family resilience is not well understood. This study examines patterns of family functioning that may protect families from the negative impact of alcohol abuse. Naturally occurring patterns of family functioning are identified and associations between these patterns and parenting, current parental alcohol use, recent family stressful events, supportive relationships outside the family, and demographic characteristics are assessed. Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
(37 reference statements)
3
14
0
2
Order By: Relevance
“…The maternal heavy alcohol use may have only taken place when the toddler was not present, for instance after bedtime or when the mother had a babysitter. A higher level of family functioning and positive parenting styles may also have been protective for the negative effect of heavy maternal alcohol use [47]. We also did not have information about the duration of the period in which the mother engaged in heavy alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…The maternal heavy alcohol use may have only taken place when the toddler was not present, for instance after bedtime or when the mother had a babysitter. A higher level of family functioning and positive parenting styles may also have been protective for the negative effect of heavy maternal alcohol use [47]. We also did not have information about the duration of the period in which the mother engaged in heavy alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…We could find only one related study in the literature, and it clustered families based on various protective factors at one point in time. Coyle et al (2009) studied families with a parent who had an alcohol problem and found that "well-functioning families" had higher scores on all measures of family regulatory processes (e.g., communication, problem solving, cohesion, adaptable roles) as well as indices of effective child rearing. Although this study suggested that family and dyadic regulatory mechanisms co-occur, it did not disentangle cause and effect because resilience (the outcome) was defined in terms of its predictors -regulatory processes that were conceptualized as protective factors (for a discussion of such tautologies, see Luthar & Zelazo, 2003).…”
Section: A Family Perspective On Resilience As Regulationmentioning
confidence: 99%
“…A Korean study which sought to clarify and delineate the concept of family resilience concludes that resilient families are those characterized by, among other things, positive outlook and a collective orientation (Lee et al 2004). Likewise, a cross-sectional study (Coyle et al 2009) of the nature of family resilience in families affected by parental alcohol abuse lends support to the importance of family beliefs or schemas in influencing a family's ability to problem-solve and cope with stressful events. Family resilience is culturally specific.…”
Section: Cultural Beliefs and Resiliencementioning
confidence: 95%